2020
DOI: 10.1136/bmjopen-2020-041563
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of pharmacists’ interventions on multidisciplinary lung transplant outpatients’ management: results of a 7-year observational study

Abstract: ObjectivesLung transplant (LT) recipients require multidisciplinary care because of the complexity of therapeutic management. Pharmacists are able to detect drug-related problems and provide recommendations to physicians through pharmacists’ interventions (PIs). We aimed at assessing the clinical impact of PIs on therapeutic management in LT outpatients.DesignData were collected prospectively from an LT recipients cohort during 7 years. A multidisciplinary committee assessed retrospectively the clinical impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…The independence of three dimensions helps to interpret the scoring results flexibly. Mongaret et al 21 and Duwez et al 22 used only the clinical dimension of the CLEO tool in their study to determine clinically significant PIs, while Zecchini et al 23 used only the clinical and economic dimensions. Another tool could take advantage of all three dimensions to demonstrate the whole effects of a PI.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The independence of three dimensions helps to interpret the scoring results flexibly. Mongaret et al 21 and Duwez et al 22 used only the clinical dimension of the CLEO tool in their study to determine clinically significant PIs, while Zecchini et al 23 used only the clinical and economic dimensions. Another tool could take advantage of all three dimensions to demonstrate the whole effects of a PI.…”
Section: Original Researchmentioning
confidence: 99%
“…User satisfaction and acceptability with the tool was high. Indeed, the CLEO tool was used easily in French hospital settings [21][22][23] and received good feedback from three Swiss hospitals. 24 However, pharmacists suggested that training with sample cases and regular discussion of real scenarios in daily practice is necessary to improve its reliability.…”
Section: Appropriateness Acceptability Feasibility and Precisionmentioning
confidence: 99%
“…More importantly, the study showed that, when accepted, a clinical pharmacist presented a positive clinical impact for 98.9% of patients, and none had a negative clinical impact. 83 The role of a pharmacist in patient-care teams can be an invaluable asset.…”
Section: Multidisciplinary Approachmentioning
confidence: 99%
“…The participation of clinical pharmacist and therapeutic drug monitoring are considered helpful in managing DDIs. 54 , 55 In patients with C 0 variation, the pharmacist informed the physician with the appropriate recommendations. In most patients, the dose of immunosuppressant was preemptively modified to maintain C 0 within the therapeutic range, therefore, not all patients, with real DDIs due to C 0 alteration, suffered toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The participation of clinical pharmacist and therapeutic drug monitoring are considered helpful in managing DDIs 54,55 . In patients with C 0 variation, the pharmacist informed the physician with the appropriate recommendations.…”
Section: Discussionmentioning
confidence: 99%